Effect of artificial saliva on the fatigue and wear response of TiAl6V4 specimens produced by SLM - Jesus, J. de (2020)
Additive manufactured (AM) parts made in TiAl6V4 alloy are increasingly used in medical prostheses and dental implants, because of its high strength, low weight and excellent biocompatibility. These components work under environmentally assisted cyclic loading, i.e. under corrosion-fatigue, and/or subject to wear conditions. Fatigue performance of additive manufactured alloys is significantly influenced by the porosities, residual stresses, which can reduce its strength when compared with traditional materials. This paper presents the results of a fatigue crack propagation study in titanium TiAl6V4 specimens produced by selective laser melting (SLM) under artificial saliva ambient. Tests were performed using standard 6 mm thick compact specimens (CT) tested at R=0.05 and with frequencies of 1 and 10 Hz. The main objective of the current research work was studying the corrosion effect on the fatigue crack propagation of Selective Laser Melting (SLM) specimens, and to compare the tribocorrosion behaviour of two different specimens: one produced by SLM and the other by the conventional/traditional method. The study concluded that: AM Titanium Ti6Al4V alloy exhibits a moderate effect of saliva ambient on fatigue crack nucleation and on fatigue crack propagation, the wear rate coefficients for SLM and conventional manufactured specimens is of the same order, and the mechanism of abrasive wear is mainly with grooves aligned with the direction of sliding.